Ultraviolet curable resin composition, method for producing light emitting device, and light emitting device

By using a cationic polymerizable compound and a cationic curing catalyst in the ultraviolet curable resin composition, combined with ultraviolet irradiation and inkjet forming method, the problem of reducing transparency in the prior art is solved, and low viscosity is achieved , high storage stability and high transparency.

CN112062936BActive Publication Date: 2025-02-25PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202010520601.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-10
Filing Date
2020-06-09
Publication Date
2025-02-25
Estimated Expiration
2040-06-09

AI Technical Summary

Technical Problem

The conventional ultraviolet curable resin composition can easily reduce the transparency of the optical component when improving the curability, and it is difficult to achieve low viscosity and high storage stability.

Method used

Using an ultraviolet curable resin composition containing a cationic polymerizable compound (F) and a cationic curing catalyst (G), the cationic polymerizable compound contains an epoxy compound and a compound having an oxyalkylene group and an oxetane group (f22) , curing properties are improved by ultraviolet irradiation, and molded by inkjet method to achieve low viscosity and high storage stability.

Benefits of technology

It is achieved that the transparency of the optical component is not reduced when the curing properties is improved, and the low viscosity can be maintained during long-term storage, the generation of poor liquid droplets in the inkjet method can be reduced, and the heat resistance and light transmittance of the sealing material can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112062936B_ABST
    Figure CN112062936B_ABST
Patent Text Reader

Abstract

The present invention provides a UV-curable resin composition, a method for manufacturing a light-emitting device, and a light-emitting device. The UV-curable resin composition can be used to make an optical component that transmits light emitted by a light source and is not easy to cause the optical component to become turbid. The UV-curable resin composition contains a cationic polymerizable compound (F) and a cationic curing catalyst (G). The cationic curing catalyst (G) contains a plurality of ionic photoacid generators whose conjugate acid strengths of anionic species are different from each other. The UV-curable resin composition is used to make an optical component that transmits light emitted by a light source.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an ultraviolet curable resin composition, a method for producing a light-emitting device, and a light-emitting device. Specifically, the present application relates to an ultraviolet curable resin composition containing a cationic polymerizable compound and a cationic curing catalyst, a method for producing a light-emitting device using the ultraviolet curable resin composition, and a light-emitting device having a sealing material containing a cured product of the ultraviolet curable resin composition. Background Art

[0002] Light-emitting devices including light-emitting elements such as organic EL elements and micro LEDs are already used for lighting, display, and the like, and are expected to become more popular in the future.

[0003] The light-emitting element in the light-emitting device is covered with a sealing material so that the light-emitting element is not degraded by moisture. In this case, the light emitted by the light-emitting element is emitted to the outside through the sealing material. The sealing material can be made of a composition containing a cation-curable resin and a cationic polymerization initiator (see Japanese Patent Gazette No. 5703429). In this case, the sealing material can be made by curing the composition by ultraviolet irradiation, etc., so that the sealing material can be made without applying a load caused by heat to the light-emitting element. Summary of the invention

[0004] The subject of the present application is: to provide an ultraviolet curable resin composition for use in preparing an optical component that transmits light emitted by a light source, which is an ultraviolet curable resin composition that is not likely to reduce the transparency of the optical component even if the curability is improved and is easy to achieve low viscosity and high storage stability; a method for manufacturing a light-emitting device using the ultraviolet curable resin composition; and a light-emitting device having an optical component containing a cured product of the ultraviolet curable resin composition.

[0005] Means for solving problems

[0006] The ultraviolet curable resin composition described in one embodiment of the present application contains a cationic polymerizable compound (F) and a cationic curing catalyst (G), wherein the cationic polymerizable compound (F) contains an epoxy compound and a compound (f22) having an oxyalkylene group and an oxetane group. The ultraviolet curable resin composition is used to make an optical component that transmits light emitted by a light source.

[0007] A method for manufacturing a light-emitting device according to one embodiment of the present application is a method for manufacturing a light-emitting device having a light-emitting element and a sealing material covering the light-emitting element. The method comprises: using an inkjet method to spray the ultraviolet curable resin composition to a position where light emitted by the light source passes to form a coating film, and irradiating the coating film with ultraviolet light to thereby form the sealing material.

[0008] A light emitting device according to one embodiment of the present application includes a light source and an optical component that transmits light emitted by the light source. The optical component includes a cured product of the ultraviolet curable resin composition. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 This is a schematic cross-sectional view showing a first example of a light emitting device in one embodiment of the present application.

[0010] Figure 2 This is a schematic cross-sectional view showing a second example of the light emitting device in one embodiment of the present application. DETAILED DESCRIPTION

[0011] The composition used to make optical components such as sealing materials is preferably low in viscosity for easy formability, and preferably does not contain easily volatile components so that the viscosity does not increase even if stored for a long time. Furthermore, in order to improve the efficiency of making optical components, it is preferred that the curability of the composition is high when irradiated with ultraviolet rays.

[0012] However, according to the inventors' research, if the curability of the cationically polymerizable composition is improved, the transparency of the optical component is likely to decrease. If the transparency of the optical component decreases, the light emitting performance of the light emitting element or the like decreases.

[0013] Therefore, the inventors have conducted intensive research and development to provide the following ultraviolet curable resin composition, which is used to produce an optical component that transmits light emitted by a light source, and is an ultraviolet curable resin composition that is not likely to reduce the transparency of the optical component even if the curability is improved and is easy to achieve low viscosity and high storage stability, and has completed the present application as a result.

[0014] Hereinafter, one embodiment of the present application will be described.

[0015] The ultraviolet curable resin composition described in this embodiment (hereinafter also referred to as composition (X)) is used to prepare an optical component that transmits light emitted by a light source. The optical component is a component for transmitting light in a device (such as a light-emitting device) having an optical system. The optical component is, for example, a sealing material for a light-emitting element. The optical component is, for example, a thin film, more specifically, a film of 2 μm or more and 50 μm or less, or a film of 2 μm or more and 30 μm or less.

[0016] The composition (X) contains a cationically polymerizable compound (F) and a cationic curing catalyst (G). The cationically polymerizable compound (F) contains an epoxy compound and a compound (f22) having an oxyalkylene group and an oxetane group.

[0017] According to the present embodiment, when the composition (X) is irradiated with ultraviolet rays, the curability of the composition (X) is easily improved, and the composition (X) at this time is not easy to cause excessively violent curing, so the cured product is not easy to produce deterioration of transparency due to white turbidity, etc. It can be inferred that the mechanism of producing this effect is as follows. The reactivity of compound (f22) is lower than that of epoxy compounds, so if ultraviolet rays are irradiated on the composition (X), the epoxy compounds react first. Through the reaction of the epoxy compounds, the curability of the composition (X) tends to become higher. Next, the compound (f22) reacts, thereby making it difficult to produce a situation where the epoxy compound and the compound (f22) react at one time. It can be considered that this is not easy to cause an overly violent reaction.

[0018] In addition, compound (f22) has low viscosity, and therefore, it is easy to reduce the viscosity of composition (X). In addition, compound (f22) is not easy to volatilize, and therefore, even if composition (X) is stored, composition (X) is not easy to change in composition due to volatilization of compound (f22). Therefore, compound (f22) is easy to improve the storage stability of composition (X).

[0019] Furthermore, for compound (f22), when the composition (X) is ejected by an inkjet method, it is not easy to generate defective droplets called satellite drops, and even if the speed of the droplets ejected by the inkjet method is increased, satellite drops are not easy to generate. In addition, as described above, compound (f22) can improve the storage stability of the composition (X), so even if the composition (X) is stored for a long time, it is easy to maintain the characteristic of the composition (X) that satellite drops are not easy to generate.

[0020] Thus, according to this embodiment, when an optical component is produced from the composition (X), even if the curability of the composition (X) is improved, the transparency of the optical component is not easily reduced, and the low viscosity and high storage stability of the composition (X) can be easily achieved.

[0021] The cured product obtained by irradiating the composition (X) with light and then heating it preferably has a glass transition temperature of 80°C or higher. In this case, the cured product can have good heat resistance. Therefore, for example, when the cured product is subjected to a treatment accompanied by a temperature rise, the cured product is not easily deteriorated. The glass transition temperature of the cured product is more preferably 90°C or higher, and further preferably 100°C or higher.

[0022] The viscosity of the composition (X) at 25°C is preferably 1 mPa·s or more and 40 mPa·s or less. In this case, the composition (X) can be formed by applying the composition (X) at room temperature by a casting method or by ejecting the composition (X) by an inkjet method. If the viscosity is 35 mPa·s or less, it is more preferred, if it is 30 mPa·s or less, it is further preferred, if it is 20 mPa·s or less, it is particularly preferred, and if it is 15 mPa·s or less, it is most preferred. The viscosity is also preferably 5 mPa·s or more, and if it is 8 mPa·s or more, it is more preferred. For example, the viscosity is preferably 8 mPa·s or more and 35 mPa·s or less.

[0023] It is also preferred that the viscosity of the composition (X) at 40°C is 1 mPa·s or more and 40 mPa·s or less. In this case, no matter what the viscosity of the composition (X) at room temperature is, the viscosity can be reduced by slightly heating the composition (X). Therefore, if heated, it is easy to form the composition (X) by a method such as a casting method, and the composition (X) can also be ejected by an inkjet method. In addition, the viscosity of the composition (X) can be reduced without significantly heating the composition (X), so that the composition (X) can be less likely to be changed due to the volatilization of the components in the composition (X). If the viscosity is 35 mPa·s or less, it is more preferred, if it is 30 mPa·s or less, it is further preferred, if it is 20 mPa·s or less, it is particularly preferred, and if it is 15 mPa·s or less, it is most preferred. It is also preferred that the viscosity is 5 mPa·s or more, and if it is 8 mPa·s or more, it is more preferred. For example, the viscosity is preferably 8 mPa·s or more and 35 mPa·s or less.

[0024] The low viscosity of the composition (X) at 25° C. or 40° C. as described above can be achieved by the composition of the composition (X) described in detail below.

[0025] The total light transmittance of the cured product of the composition (X) is preferably 90% or more when the thickness dimension is 10 μm. In this case, if the cured product is applied to an optical component such as the sealing material 5 in the light-emitting device 1, the extraction efficiency of light emitted to the outside through the optical component can be particularly improved. The light transmittance of the cured product as described above can also be achieved by the composition of the composition (X) described in detail below.

[0026] The surface tension of the composition (X) is also preferably 20 mN / cm or more and 40 mN / cm or less. In this case, when the composition (X) is ejected by an inkjet method, the ejection stability is good and it is not easy to produce bad droplets called satellite drops. If the surface tension is 30 mN / cm or more and 40 mN / cm or less, it is more preferred, and if it is 31 mN / cm or more and 38 mN / cm or less, it is further preferred.

[0027] Hereinafter, this embodiment will be described in further detail.

[0028] 1. Structure of the light-emitting device

[0029] First, the structure of the light-emitting device 1 is described in the case where the device having an optical system is a light-emitting device 1 and the optical component is a sealing material 5 that seals the light-emitting element 4 in the light-emitting device 1. The light-emitting device 1 includes a light-emitting element 4 and a sealing material 5 that covers the light-emitting element 4. The sealing material 5 may cover the light-emitting element 4 in a state of directly contacting the light-emitting element 4, or may cover the light-emitting element 4 in a state of sandwiching some layer between the sealing material 5 and the light-emitting element 4. The light-emitting device 1 may be, for example, a lighting device or a display device (display).

[0030] The light emitting element 4 includes, for example, a light emitting diode. The light emitting diode includes, for example, at least one of an organic EL element (organic light emitting diode) and a micro light emitting diode. When the light emitting element 4 includes an organic light emitting diode, the light emitting device 1 including the light emitting element 4 is, for example, an organic EL display. When the light emitting element 4 includes a micro light emitting diode, the light emitting device 1 including the light emitting element 4 is, for example, a micro LED display. It should be noted that EL refers to electroluminescence and LED refers to a light emitting diode.

[0031] Reference Figure 1 A first example of the structure of the light emitting device 1 is described. The light emitting device 1 is a top emission type. The light emitting device 1 includes a supporting substrate 2, a transparent substrate 3 opposed to the supporting substrate 2 with a gap therebetween, a light emitting element 4 located on the surface of the supporting substrate 2 opposed to the transparent substrate 3, and a sealing material 5 filled between the supporting substrate 2 and the transparent substrate 3. In addition, in the first example, the light emitting device 1 includes a passivation layer 6 covering the surface of the supporting substrate 2 opposed to the transparent substrate 3 and the light emitting element 4. That is, the passivation layer 6 is sandwiched between the light emitting element 4 and the sealing material 5 covering the light emitting element 4.

[0032] The support substrate 2 is made of, for example, a resin material, but is not limited thereto. The transparent substrate 3 is made of a light-transmitting material. The transparent substrate 3 is, for example, a glass substrate or a transparent resin substrate. When the light-emitting element 4 includes an organic EL element, the organic EL element includes, for example, a pair of electrodes and an organic light-emitting layer located between the electrodes. The organic light-emitting layer includes, for example, a hole injection layer, a hole transport layer, an organic light-emitting layer, and an electron transport layer, and these layers are stacked in the above order. Figure 1 Only one light emitting element 4 is shown in FIG. 1 , but the light emitting device 1 may include a plurality of light emitting elements 4, and the plurality of light emitting elements 4 may form an array on the support substrate 2. The passivation layer 6 is preferably made of silicon nitride or silicon oxide.

[0033] Reference Figure 2 A second example of the structure of the light emitting device 1 is described. Figure 1 The common elements of the first example shown are Figure 2 In the endowment Figure 1 The same symbols are used and detailed descriptions are appropriately omitted. Figure 2 The light emitting device 1 shown is also a top emission type and includes a supporting substrate 2, a transparent substrate 3 spaced apart from the supporting substrate 2, a light emitting element 4 located on the surface of the supporting substrate 2 facing the transparent substrate 3, and a sealing material 5 covering the light emitting element 4.

[0034] When the light emitting element 4 includes an organic EL element, the organic EL element includes, for example, a pair of electrodes 41 and 43, and an organic light emitting layer 42 located between the electrodes 41 and 43, as in the first example. The organic light emitting layer 42 includes, for example, a hole injection layer 421, a hole transport layer 422, an organic light emitting layer 423, and an electron transport layer 424, and these layers are stacked in the above order.

[0035] The light-emitting device 1 includes a plurality of light-emitting elements 4, and the plurality of light-emitting elements 4 form an array 9 (hereinafter referred to as the element array 9) on the supporting substrate 2. The element array 9 also includes a partition wall 7. The partition wall 7 is located on the supporting substrate 2 and separates two adjacent light-emitting elements 4. The partition wall 7 is made, for example, by forming a photosensitive resin material using a photolithography method. The element array 9 also includes a connection wiring 8 that electrically connects the electrodes 43 and the electron transport layer 424 of the adjacent light-emitting elements 4 to each other. The connection wiring 8 is provided on the partition wall 7.

[0036] The light emitting device 1 further includes a passivation layer 6 covering the light emitting element 4. The passivation layer 6 is preferably made of silicon nitride or silicon oxide. The passivation layer 6 includes a first passivation layer 61 and a second passivation layer 62. The first passivation layer 61 covers the element array 9 in a state of directly contacting the element array 9, thereby covering the light emitting element 4. The second passivation layer 62 is arranged at a position opposite to the element array 9 relative to the first passivation layer 61, and a gap is separated between the second passivation layer 62 and the first passivation layer 61. The sealing material 5 is filled between the first passivation layer 61 and the second passivation layer 62. That is, the first passivation layer 61 is sandwiched between the light emitting element 4 and the sealing material 5 covering the light emitting element 4.

[0037] Furthermore, a second sealing material 52 is filled between the second passivation layer 62 and the transparent substrate 3. The second sealing material 52 is made of, for example, a transparent resin material. There is no particular limitation on the material of the second sealing material 52. The material of the second sealing material 52 can be the same as that of the sealing material 5 or different.

[0038] The sealing material 5 in the light-emitting device 1 having the structure exemplified above can be prepared from the composition (X). That is, the composition (X) is used to prepare the sealing material 5 for the light-emitting element 4. Furthermore, in other words, the composition (X) is preferably a composition for preparing a sealing material, a composition for sealing a light-emitting element, or a composition for manufacturing a light-emitting device.

[0039] 2. Ultraviolet curable resin composition

[0040] The composition (X) contains a curable component having ultraviolet curability. The curable component contains a cationically polymerizable compound (F) and a cationic curing catalyst (photocationic curing catalyst) (G).

[0041] As described above, the cationically polymerizable compound (F) contains the epoxy compound (f1) and the compound (f22) having an oxyalkylene group and an oxetane group.

[0042] In addition, the cationic polymerizable compound (F) contains, for example, at least one of a polyfunctional cationic polymerizable compound (F1) and a monofunctional cationic polymerizable compound (F2). The polyfunctional cationic polymerizable compound (F1) and the monofunctional cationic polymerizable compound (F2) specify the components contained in the cationic polymerizable compound (F) based on the number of functional groups in one molecule. Therefore, the above-mentioned epoxy compound (f1) can contain at least one of the components contained in the polyfunctional cationic polymerizable compound (F1) and the components contained in the monofunctional cationic polymerizable compound (F2). In addition, the compound (f22) having an oxyalkylene group and an oxetane group can also contain at least one of the components contained in the polyfunctional cationic polymerizable compound (F1) and the components contained in the monofunctional cationic polymerizable compound (F2).

[0043] The polyfunctional cationically polymerizable compound (F1) may contain either or both of a polyfunctional cationically polymerizable compound (F11) not having a siloxane skeleton and a polyfunctional cationically polymerizable compound (F12) having a siloxane skeleton.

[0044] The polyfunctional cationically polymerizable compound (F11) does not have a siloxane skeleton and has two or more cationically polymerizable functional groups per molecule. The number of cationically polymerizable functional groups per molecule of the polyfunctional cationically polymerizable compound (F11) is preferably 2 to 4, and more preferably 2 to 3.

[0045] The cationically polymerizable functional group is, for example, at least one group selected from an epoxy group, an oxetane group, and a vinyl ether group.

[0046] The polyfunctional cationically polymerizable compound (F11) contains, for example, at least one compound selected from the group consisting of polyfunctional alicyclic epoxy compounds, polyfunctional heterocyclic epoxy compounds, polyfunctional oxetane compounds, alkylene glycol diglycidyl ethers, and alkylene glycol monovinyl monoglycidyl ethers.

[0047] The polyfunctional alicyclic epoxy compound contains, for example, either or both of a compound represented by the following formula (1) and a compound represented by the following formula (20).

[0048]

[0049] In formula (1), R 1 ~R 18 Each is independently a hydrogen atom, a halogen atom or a hydrocarbon group. The number of carbon atoms in the hydrocarbon group is preferably in the range of 1 to 20. Examples of hydrocarbon groups are alkyl groups having 1 to 20 carbon atoms such as methyl, ethyl, and propyl groups; alkenyl groups having 2 to 20 carbon atoms such as vinyl and allyl groups; or alkylidene groups having 2 to 20 carbon atoms such as ethylidene and propylidene groups. The hydrocarbon group may contain an oxygen atom or a halogen atom. R 1 ~R 18 Each independently is preferably a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms, more preferably a hydrogen atom or a methyl group, and most preferably a hydrogen atom.

[0050] In formula (1), X is a single bond or a divalent organic group, and an example of the organic group is -CO-O-CH2-.

[0051] Examples of the compound represented by the formula (1) include a compound represented by the following formula (1a) and a compound represented by the following formula (1b).

[0052]

[0053]

[0054] In formula (20), R 1 ~R 12 Each is independently a hydrogen atom, a halogen atom or a hydrocarbon group having 1 to 20 carbon atoms. Examples of the halogen atom are fluorine atoms, chlorine atoms, bromine atoms or iodine atoms. Examples of the hydrocarbon group having 1 to 20 carbon atoms are alkyl groups having 1 to 20 carbon atoms such as methyl, ethyl and propyl groups; alkenyl groups having 2 to 20 carbon atoms such as vinyl and allyl groups; or alkylidene groups having 2 to 20 carbon atoms such as ethylidene and propylidene groups. The hydrocarbon group having 1 to 20 carbon atoms may contain an oxygen atom or a halogen atom.

[0055] R 1 ~R 12 Each independently is preferably a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms, more preferably a hydrogen atom or a methyl group, and most preferably a hydrogen atom.

[0056] Examples of the compound represented by the formula (20) include tetrahydroindene diepoxide represented by the following formula (20a).

[0057]

[0058] The polyfunctional heterocyclic epoxy compound includes, for example, a trifunctional epoxy compound represented by the following formula (2).

[0059]

[0060] The polyfunctional oxetane compound includes, for example, a bifunctional oxetane compound represented by the following formula (3).

[0061]

[0062] The alkylene glycol diglycidyl ether contains, for example, at least one compound selected from the group consisting of compounds represented by the following formulae (4) to (7).

[0063]

[0064] The alkylene glycol monovinyl monoglycidyl ether includes, for example, a compound represented by the following formula (8).

[0065]

[0066] More specifically, the multifunctional cationic polymerizable compound (F11) may contain, for example, at least one component selected from CELLOXIDE 2021P and CELLOXIDE 8010 manufactured by Daicel, TEPIC-VL manufactured by Nissan Chemical, OXT-221 manufactured by Toagosei, and 1,3-PD-DEP, 1,4-BG-DEP, 1,6-HD-DEP, NPG-DEP and butanediol monovinyl monoglycidyl ether manufactured by Yokkaichi Kogyo.

[0067] The polyfunctional cationically polymerizable compound (F11) preferably further contains a polyfunctional alicyclic epoxy compound. In this case, the composition (X) can have particularly high cationic polymerization reactivity.

[0068] The polyfunctional alicyclic epoxy compound particularly preferably contains one or both of the compound represented by formula (1) and the compound represented by formula (20). In this case, the composition (X) can have higher cationic polymerization reactivity.

[0069] When the polyfunctional alicyclic epoxy compound contains a compound represented by formula (1), the compound represented by formula (1) preferably contains a compound represented by formula (1a). In this case, the composition (X) can have higher cationic polymerization reactivity and particularly low viscosity.

[0070] In addition, in particular, because the compound shown in formula (20) has low viscosity, when containing the compound shown in formula (20), the composition (X) can have good ultraviolet curability and can have particularly low viscosity. Furthermore, the compound shown in formula (20) has low viscosity, but has a property of being difficult to volatilize. Therefore, even if the composition (X) contains the compound shown in formula (20), the composition (X) is not easy to produce changes in the composition caused by the volatilization of the compound shown in formula (20). Therefore, the composition (X) can achieve low viscosity without damaging storage stability by containing the compound shown in formula (20).

[0071] The compound represented by the formula (20) can be synthesized, for example, by oxidizing a cyclic olefin compound having a tetrahydroindene skeleton using an oxidizing agent.

[0072] The compound represented by formula (20) can contain 4 stereoisomers based on the stereo configuration of 2 epoxy rings. The compound represented by formula (20) can contain any of the 4 stereoisomers. That is, the compound represented by formula (20) can contain at least one component selected from the 4 stereoisomers. The ratio of the total amount of the exo-endo form and the endo-endo form in the 4 stereoisomers in the compound represented by formula (20) is preferably 10% by mass or less relative to the epoxy compound (A1) as a whole, and if it is 5% by mass or less, it is further preferred. In this case, the heat resistance of the cured product can be improved. It should be noted that the ratio of a specific stereoisomer in the compound represented by formula (20) can be obtained based on the peak area ratio appearing in the chromatogram obtained by gas chromatography.

[0073] In order to reduce the amount of exo-endo and endo-endo in the compound represented by formula (20), the following appropriate methods can be applied: a method of precisely distilling the compound represented by formula (20) or a method of applying column chromatography using silica gel or the like as a filler.

[0074] When the composition (X) contains a polyfunctional cationic polymerizable compound (F11), the ratio of the polyfunctional cationic polymerizable compound (F11) to the total amount of the resin component is preferably in the range of 5 to 95% by mass. It should be noted that the resin component refers to a cationic polymerizable compound in the composition (X), including a polyfunctional cationic polymerizable compound (F1) and a monofunctional cationic polymerizable compound (F2). If the ratio of the polyfunctional cationic polymerizable compound (F11) is 5% by mass or more, the composition (X) can have particularly excellent reactivity during photocationic polymerization, and thereby, the cured product can have high strength (hardness). In addition, if the ratio of the polyfunctional cationic polymerizable compound (F11) is 95% by mass or less, when the composition (X) contains a hygroscopic agent (C), it is easy to make the hygroscopic agent (C) particularly uniformly dispersed in the composition (X). For the proportion of the multifunctional cationic polymerizable compound (F11), if it is 12% by mass or more, it is more preferred, if it is 15% by mass or more, it is further preferred, if it is 20% by mass or more, it is further preferred, and if it is 25% by mass or more, it is particularly preferred. In addition, for the proportion of the multifunctional cationic polymerizable compound (F11), if it is 85% by mass or less, it is more preferred, and if it is 60% by mass or less, it is further preferred. For example, the proportion of the multifunctional cationic polymerizable compound (F11) is preferably in the range of 20 to 60% by mass.

[0075] When the polyfunctional cationically polymerizable compound (F11) contains a polyfunctional alicyclic epoxy compound, the polyfunctional alicyclic epoxy compound may be a part of the polyfunctional cationically polymerizable compound (F11) or the whole of the polyfunctional cationically polymerizable compound (F11). The ratio of the polyfunctional alicyclic epoxy compound to the polyfunctional cationically polymerizable compound (F11) is preferably in the range of 15 to 100% by mass. If the ratio is 15% by mass or more, the polyfunctional alicyclic epoxy compound can particularly contribute to the improvement of the ultraviolet curability of the composition (X).

[0076] The multifunctional cationic polymerizable compound (F12) has a siloxane skeleton and two or more cationic polymerizable functional groups in each molecule. The number of cationic polymerizable functional groups in each molecule of the multifunctional cationic polymerizable compound (F12) is preferably 2 to 6, and is further preferably 2 to 4. The multifunctional cationic polymerizable compound (F12) can contribute to the improvement of the cationic polymerization reactivity of the composition (X), and can contribute to the improvement of the heat discoloration resistance of the cured product and the optical component. The multifunctional cationic polymerizable compound (F12) can also contribute to the low elastic modulus of the cured product and the optical component. When the composition (X) contains a hygroscopic agent, the multifunctional cationic polymerizable compound (F12) can also contribute to the improvement of the dispersibility of the hygroscopic agent in the composition (X) and in the cured product.

[0077] The polyfunctional cationically polymerizable compound (F12) is preferably liquid at 25° C. In particular, the viscosity of the polyfunctional cationically polymerizable compound (F12) at 25° C. is preferably within a range of 10 to 300 mPa■s. In this case, an increase in the viscosity of the composition (X) can be suppressed.

[0078] The cationically polymerizable functional group possessed by the polyfunctional cationically polymerizable compound (F12) is, for example, at least one group selected from the group consisting of an epoxy group, an oxetane group, and a vinyl ether group.

[0079] The siloxane skeleton possessed by the multifunctional cationic polymerizable compound (F12) may be linear, branched, or cyclic. The number of Si atoms possessed by the siloxane skeleton is preferably in the range of 2 to 14. In this case, the composition (X) may have a particularly low viscosity. If the number of Si atoms is in the range of 2 to 10, it is more preferred, if it is in the range of 2 to 7, it is further preferred, and if it is in the range of 3 to 6, it is particularly preferred.

[0080] The polyfunctional cationically polymerizable compound (F12) contains, for example, at least one of a compound represented by the formula (10) and a compound represented by the formula (11).

[0081]

[0082] R in each of formula (10) and formula (11) is a single bond or a divalent organic group, preferably an alkylene group. Y is a siloxane skeleton, which may be any of a linear, branched, and cyclic structure, and the number of Si atoms is preferably in the range of 2 to 14, more preferably in the range of 2 to 10, further preferably in the range of 2 to 7, and particularly preferably in the range of 3 to 6. n is an integer greater than 2, preferably in the range of 2 to 4.

[0083] More specifically, for example, the polyfunctional cationically polymerizable compound (F12) contains a compound represented by the following formula (10a).

[0084]

[0085] R in formula (10a) is a single bond or a divalent organic group, and is preferably an alkylene group having 1 to 4 carbon atoms. n in formula (10a) is an integer greater than 0. n is preferably in the range of 0 to 12, more preferably in the range of 0 to 8, further preferably in the range of 0 to 5, and particularly preferably in the range of 1 to 4.

[0086] More specifically, the polyfunctional cationic polymerizable compound (F12) preferably contains at least one component selected from the group consisting of models X-40-2669, X-40-2670, X-40-2715, X-40-2732, X-22-169AS, X-22-169B, X-22-2046, X-22-343, X-22-163, and X-22-163B manufactured by Shin-Etsu Chemical Co., Ltd.

[0087] The polyfunctional cationic polymerizable compound (F12) preferably has an alicyclic epoxy structure, and it is particularly preferred if the polyfunctional cationic polymerizable compound (F12) contains a compound represented by formula (10a). The compound represented by formula (10a) can be particularly helpful in improving the cationic polymerization reactivity and reducing the viscosity of the composition (X), and can be particularly helpful in improving the heat discoloration resistance and reducing the elastic modulus of the cured product and optical components. When the composition (X) contains a hygroscopic agent (C), it can also be particularly helpful in improving the dispersibility of the hygroscopic agent (C) in the composition (X).

[0088] When the composition (X) contains a polyfunctional cationically polymerizable compound (F12), the ratio of the polyfunctional cationically polymerizable compound (F12) to the total amount of the resin component is preferably in the range of 5 to 95% by mass. In this case, especially when the composition (X) contains a hygroscopic agent (C), the dispersibility of the hygroscopic agent (C) in the composition (X) and in the cured product is particularly improved, and the composition (X) can have a particularly high photocationic polymerization reactivity.

[0089] The monofunctional cationically polymerizable compound (F2) has only one cationically polymerizable functional group in one molecule. The cationically polymerizable functional group is, for example, at least one group selected from the group consisting of an epoxy group, an oxetane group, and a vinyl ether group.

[0090] The viscosity of the monofunctional cationically polymerizable compound (F2) at 25°C is preferably 8 mPa·s or less. In this case, even if the composition (X) does not contain a solvent, the monofunctional cationically polymerizable compound (F2) can reduce the viscosity of the composition (X). In particular, the viscosity of the monofunctional cationically polymerizable compound (F2) at 25°C is preferably in the range of 0.1 to 8 mPa·s.

[0091] The monofunctional cationically polymerizable compound (F2) may contain, for example, at least one compound selected from the group consisting of compounds represented by the following formulae (12) to (17) and limonene oxide.

[0092]

[0093] The ratio of the monofunctional cationically polymerizable compound (F2) to the total amount of the resin component is preferably in the range of 5 to 50% by mass. If the ratio of the monofunctional cationically polymerizable compound (F2) is 5% by mass or more, the viscosity of the composition (X) can be particularly reduced. In addition, if the ratio of the monofunctional cationically polymerizable compound (F2) is 50% by mass or less, the composition (X) can have particularly excellent reactivity during the photocationic polymerization reaction, and thereby, the cured product can have high strength (hardness). If the ratio of the monofunctional cationically polymerizable compound (F2) is 10% by mass or more, it is more preferred, and if it is 15% by mass or more, it is further preferred. In addition, if the ratio of the monofunctional cationically polymerizable compound (F2) is 40% by mass or less, it is more preferred, if it is 35% by mass or less, it is further preferred, and if it is 30% by mass or less, it is particularly preferred. If the proportion of the monofunctional cationically polymerizable compound (F2) is particularly 35% by mass or less, the volatilization amount of the components in the composition (X) during the storage of the composition (X) can be effectively reduced, so that even if the composition (X) is stored for a long time, the properties of the composition (X) are not easily damaged. Furthermore, the stickiness of the cured product can be particularly suppressed. For example, the proportion of the monofunctional cationically polymerizable compound (F2) is preferably in the range of 10 to 35% by mass.

[0094] The cationic polymerizable compound (F) may not contain a monofunctional cationic polymerizable compound (F2). In the present embodiment, even if the cationic polymerizable compound (F) does not contain a monofunctional cationic polymerizable compound (F2), even if the curability of the composition (X) is improved, the transparency of the optical component can be reduced, and the composition (X) can be easily made to have a low viscosity and high storage stability.

[0095] In addition, particularly when the composition (X) contains a polyfunctional cationic polymerizable compound (F11) and a polyfunctional cationic polymerizable compound (F12), the ratio of the polyfunctional cationic polymerizable compound (F11) is preferably in the range of 30 to 60% by mass, the ratio of the polyfunctional cationic polymerizable compound (F12) is preferably in the range of 15 to 30% by mass, and the ratio of the monofunctional cationic polymerizable compound (F2) is preferably in the range of 15 to 40% by mass, relative to the total amount of the resin component. In this case, the good storage stability, low viscosity and good cationic polymerization reactivity of the composition (X) can be well balanced, and further, the excellent transparency, excellent hygroscopicity and high refractive index of the cured product can be well balanced.

[0096] If the cationically polymerizable compound (F) contains a compound represented by formula (3) and a compound represented by formula (16), by adjusting the ratio of the two, the ease of the curing reaction when a photocured material is prepared from the composition (X) can be appropriately adjusted, and the viscosity of the composition (X) can be reduced and the storage stability can be improved.

[0097] The amount of the compound represented by formula (16) can be appropriately adjusted so that the composition (X) has the above-mentioned properties. For example, the amount of the compound represented by formula (16) is preferably 10% by mass or more and 40% by mass or less based on the total amount of the resin component.

[0098] The cationically polymerizable compound (F) preferably contains a compound (f11) represented by the following formula (30) (hereinafter also referred to as an aromatic epoxy compound (f11)).

[0099]

[0100] In formula (30), X is at least one selected from halogen, H, hydrocarbon group and alkylene glycol group. When there are multiple X in one molecule, they may be the same or different. The hydrocarbon group is, for example, an alkyl group or an aryl group. When X is a hydrocarbon group, the carbon number of X is, for example, in the range of 1 to 10. R is a single bond or a divalent organic group. When R is a divalent organic group, the divalent organic group is, for example, an alkylene group, an oxyalkylene group, a carbonyloxyalkylene group (for example, -CO-O-CH2-), or a -C(Ph)2-O-CH2- group. It is particularly preferred if the divalent organic group is -CH2-, -O-CH2- or -CO-O-CH2-. Y is H or a monovalent organic group. When Y is a monovalent organic group, the monovalent organic group is, for example, an alkyl group or an aryl group.

[0101] If the cationic polymerizable compound (F) contains an aromatic epoxy compound (f11), since the aromatic epoxy compound (f11) has a low viscosity, the aromatic epoxy compound (f11) is easy to make the composition (X) low in viscosity. In addition, the aromatic epoxy compound (f11) is not easy to volatilize, so even if the composition (X) is stored, the composition (X) is not easy to produce changes in composition due to the volatilization of the aromatic epoxy compound (f11). Therefore, the aromatic epoxy compound (f11) is easy to improve the storage stability of the composition (X). In addition, the aromatic epoxy compound (f11) has high reactivity, so it is not easy for unreacted components to remain in the cured product, and therefore, it is not easy to produce outgassing from the cured product. Furthermore, the aromatic epoxy compound (f11) is easy to increase the glass transition temperature of the cured product, so it is easy to improve the heat resistance of the cured product.

[0102] In addition, for the aromatic epoxy compound (f11), when the composition (X) is ejected by an inkjet method, undesirable droplets called satellite drops are not easily generated. Satellite droplets refer to droplets that are separated from the original droplets and attached to a position in the coating object different from the attachment position of the original droplets when the droplets are ejected by an inkjet method. If satellite droplets are generated, the dimensional accuracy of optical components such as sealing materials produced from the composition (X) will be deteriorated.

[0103] R in formula (30) is preferably a single bond or an alkylene group. When n in formula (30) is 2 or 3, at least one of the multiple Rs in formula (30) is preferably a single bond or an alkylene group. In these cases, the reactivity of the aromatic epoxy compound (111) tends to be high, and therefore, the curability of the composition (X) when the composition (X) is irradiated with ultraviolet rays tends to be high.

[0104] The aromatic epoxy compound (111) preferably contains at least one compound selected from the group consisting of compounds represented by the following formulae (301) to (318), for example.

[0105]

[0106] In particular, the aromatic epoxy compound (f11) preferably contains at least one component selected from the compounds represented by formulae (301) to (305), (312), (314) and (318). These compounds are likely to have high reactivity by bonding the epoxy group (ethylene oxide) in the compound to the benzene ring using a single bond or an alkylene group, and thus are likely to improve the curability of the composition (X).

[0107] The cationically polymerizable compound (F) contains a compound (f2) having an oxyalkylene skeleton. The oxyalkylene skeleton refers to a linear skeleton containing one or more linear oxyalkylene units.

[0108] If the cationic polymerizable compound (F) contains the compound (f2), since the compound (f2) has a low viscosity, the compound (f2) can easily reduce the viscosity of the composition (X). In addition, since the compound (f2) is not easily volatile, even if the composition (X) is stored, the composition (X) is not easily changed due to the volatilization of the compound (f2). Therefore, the compound (f2) can easily improve the storage stability of the composition (X).

[0109] In addition, for compound (f2), when the composition (X) is ejected by inkjet method, it is not easy to produce bad droplets called satellite drops. Furthermore, for compound (f2), even if the speed of the droplets ejected by inkjet method is accelerated, satellite drops can be difficult to produce. Therefore, although it is different based on the conditions of inkjet, it is also possible to make the ejection speed of the droplets based on inkjet method reach 4m / s or more without producing satellite drops. If the speed of the droplets can be accelerated, the trajectory of the droplets is not easily affected by interference, so the dimensional accuracy of optical parts such as sealing materials made by the composition (X) can be improved. And then, as described above, compound (f2) can improve the storage stability of the composition (X), therefore, even if the composition (X) is kept for a long period of time, it is easy to maintain the characteristic of the composition (X) that is not easy to produce satellite drops.

[0110] The oxyalkylene skeleton particularly preferably contains the structure "-CCO-", i.e., an oxymethylene unit. In this case, satellite droplets are particularly unlikely to be generated, for example, even if the drive frequency when the composition (X) is ejected by the inkjet method is changed, satellite droplets are unlikely to be generated. In addition, the compound (f2) is less volatile and can easily achieve a lower viscosity, and further, the affinity (wettability) of the composition (X) for inorganic materials can be easily improved.

[0111] The number of oxyalkylene units in the oxyalkylene skeleton in the compound (f2) is preferably 1 to 8. In this case, the compound (f2) tends to have a lower viscosity, and therefore, satellite drops are particularly unlikely to be generated, and the crosslinking density of the cured product tends to be high, thereby the glass transition temperature of the cured product tends to be particularly high. The number of oxyalkylene units is more preferably 1 to 6, and even more preferably 1 to 4.

[0112] It should be noted that a substituent other than hydrogen may be bonded to the oxyalkylene unit in the oxyalkylene skeleton in compound (f2). For example, the oxymethylene unit contained in the oxyalkylene skeleton may have a structure of "-CH(CH3)-CH2-O-".

[0113] The ratio of compound (f2) is preferably 10% by mass or more relative to the cationic polymerizable compound (F). In this case, the inkjet property becomes good, and the wettability to the substrate becomes better. The ratio is also preferably below 70% by weight. In this case, it is easy to increase the glass transition temperature of the optical component. If the ratio is 15% by mass or more and 60% by mass or less, it is more preferred, and if it is 20% by mass or more and 50% by mass or less, it is further preferred.

[0114] Compound (f2) contains a compound (f22) having an oxyalkylene group and an oxetane group. That is, the cationic polymerizable compound (F) contains a compound (f22) having an oxyalkylene group and an oxetane group. Compound (f2) may further contain a compound (f21) having an oxyalkylene skeleton and an epoxy group.

[0115] Compound (f21) contains, for example, at least one compound selected from the group consisting of the compound represented by formula (1b), the compound represented by formula (4), the compound represented by formula (5), the compound represented by formula (6), the compound represented by formula (7), the compound represented by formula (8), the compound represented by formula (13), the compound represented by formula (14), etc. It should be noted that the components that compound (f221) can contain are not limited to the above components.

[0116] Compound (f22) contains, for example, at least one compound selected from the group consisting of the compound represented by formula (3), the compound represented by formula (12), the compound represented by formula (16), and the compound represented by formula (17). It should be noted that the components that compound (f22) can contain are not limited to the above components.

[0117] As described above, the cationically polymerizable compound (F) contains the epoxy compound (f1) and the compound (f22). The epoxy compound (f1) contains, for example, at least one compound having an epoxy group among the compounds that the cationically polymerizable compound (F) can contain.

[0118] The ratio of compound (f22) relative to the cationic polymerizable compound (F) is preferably 10% by mass or more. In this case, the use of compound (f22) makes it particularly easy to reduce the viscosity of the composition (X) and to improve the storage stability of the composition (X). Furthermore, the use of compound (f22) makes it particularly easy to improve the curability of the composition (X). The ratio of compound (f22) is also preferably 90% by mass or less. In this case, the curability of the cured product can be fully improved. If the ratio of compound (f22) is 10% by mass or more and 90% by mass or less, it is more preferred, and if it is 20% by mass or more and 80% by mass or less, it is further preferred.

[0119] In addition, the proportion of epoxy compound (f1) is preferably 10% by mass or more and 90% by mass or less relative to the total amount of cationic polymerizable compound (F), more preferably 20% by mass or more and 80% by mass or less, and further preferably 25% by mass or more and 75% by mass or less. In these cases, the unreacted groups in the cured product can be fully reduced, and the curability of the cured product can be fully improved.

[0120] The epoxy compound (f1) preferably contains a compound having at least one oxirane ring that does not constitute a glycidyl ether group. In this case, the epoxy compound is particularly easy to improve the curability of the composition (X). It is more preferred if the epoxy compound contains a compound having 2 or more oxirane rings that do not constitute a glycidyl ether group. The epoxy compound also preferably contains a compound that does not have a glycidyl ether group. It is particularly preferred if the epoxy compound contains a compound having 2 or more oxirane rings that do not constitute a glycidyl ether group and does not have a glycidyl ether group.

[0121] It is particularly preferred that the epoxy compound (f1) contains the aromatic epoxy compound (f11). In this case, the composition (X) is likely to have particularly excellent storage stability, and when the composition (X) is ejected by an inkjet method, it is particularly difficult to generate undesirable droplets called satellite drops. Furthermore, even if the speed of the droplets ejected by the inkjet method is increased, satellite drops are particularly difficult to generate. Furthermore, even if the composition (X) is stored for a long period of time, it is particularly easy to maintain the characteristic of the composition (X) that satellite drops are not easily generated.

[0122] The total ratio of the aromatic epoxy compound (f11) and the compound (f22) to the cationic polymerizable compound (F) is preferably 55% by mass or more. In this case, the effect of the combination of the aromatic epoxy compound (f11) and the compound (f22) can be particularly significantly obtained. If the ratio is 60% by mass or more, it is more preferred, and if it is 70% by mass or more, it is further preferred. If the cationic polymerizable compound (F) contains only the aromatic epoxy compound (f11) and the compound (f22), it is particularly preferred.

[0123] The cationic curing catalyst (G) is not particularly limited as long as it is a catalyst that generates a protonic acid or a Lewis acid upon exposure to light. The cationic curing catalyst (G) contains an ionic photoacid generator. The cationic curing catalyst (G) may further contain a nonionic photoacid generator.

[0124] The ionic photoacid generator may contain at least one of an onium salt and an organic metal complex. Examples of onium salts include aromatic diazonium salts, aromatic halogen onium salts, and aromatic sulfonium salts. Examples of organic metal complexes include iron-allene complexes, titanocene complexes, and arylsilanol-aluminum complexes. The ionic photoacid generator may contain at least one of these components.

[0125] The nonionic photoacid generator may contain, for example, at least one component selected from nitrobenzyl esters, sulfonic acid derivatives, phosphoric acid esters, phenolsulfonic acid esters, naphthoquinone diazide, and N-hydroxyimidophosphonic acid esters.

[0126] More specific examples of the compound that can be contained in the cationic curing catalyst (G) include DPI series (105, 106, 109, 201, etc.), BI-105, MPI series (103, 105, 106, 109, etc.), BBI series (101, 102, 103, 105, 106, 109, 110, 200, 210, 300, 301, etc.), TSP series (102, 103, 105, 106, 109, 200, 300, 1000, etc.), HDS-109, MDS series (103, 105, 109, 203, 205, 209, etc.), BDS-109, MNPS-109, DTS series (102, 103, 105, 200, etc.), NDS series (103, 105, 155, 165, etc.), DAM series (101, 102, 103, 105 , 201, etc.), SI series (105, 106, etc.), PI-106, NDI series (105, 106, 109, 1001, 1004, etc.), PAI series (01, 101, 106, 1001, 1002, 1003, 1004, etc.), MBZ-101, PYR-100, NB series (101, 201, etc.), NAI series (100, 1002, 1 003, 1004, 101, 105, 106, 109, etc.), TAZ series (100, 101, 102, 103, 104, 107, 108, 109, 110, 113, 114, 118, 122, 123, 203, 204, etc.), NBC-101, ANC-101, TPS-Acetate, DTS-Acetate, Di-Boc Bisphinol A, tert-Butyl lithocholate, tert-Butyl deoxycholate, tert-Butyl cholate, BX, BC-2, MPI-103, BDS-105, TPS-103, NAT-103, BMS-105, and TMS-105;

[0127] CYRACURE UVI-6970, CYRACURE UVI-6974, CYRACURE UVI-6990, and CYRACURE UVI-950 manufactured by Union Carbide Corporation of the United States;

[0128] IRGACURE 250, IRGACURE 261 and IRGACURE 264 manufactured by BASF;

[0129] CG-24-61 made by CIBA-GEIGYAG;

[0130] ADEKA OPTOMER SP-150, ADEKA OPTOMER SP-151, ADEKA OPTOMER SP-170 and ADEKA OPTOMER SP-171 manufactured by ADEKA Co., Ltd.;

[0131] DAICAT II manufactured by Daicel Co., Ltd.;

[0132] UVAC1590 and UVAC1591 manufactured by Daicel Cytech Company Ltd.;

[0133] CI-2064, CI-2639, CI-2624, CI-2481, CI-2734, CI-2855, CI-2823, CI-2758, and CIT-1682 manufactured by Nippon Soda Co., Ltd.;

[0134] Toluoylcumyl iodonium tetrakis(pentafluorophenyl)borate, i.e., PI-2074, manufactured by RHODIA;

[0135] FFC509 made by 3M;

[0136] CD-1010, CD-1011 and CD-1012 made by Sartomer of the United States;

[0137] CPI-100P, CPI-101A, CPI-110P, CPI-110A and CPI-210S manufactured by San-Apro Co., Ltd.; and

[0138] UVI-6992 and UVI-6976 manufactured by Dow Chemical Company. The cationic curing catalyst (G) may contain at least one compound selected from these compounds.

[0139] Cationic curing catalyst (G) preferably contains multiple ionic photoacid generators with different intensities of the conjugated acid of anionic species. In this case, among multiple ionic photoacid generators, the ionic photoacid generator with higher intensity of conjugated acid can improve the reactivity of composition (X), therefore, it is possible to improve the efficiency of optical components made by composition (X). In addition, if composition (X) contains the above-mentioned multiple ionic photoacid generators, then in the storage of composition (X), composition (X) is not easy to gel, that is, the storage stability of composition (X) is not easy to reduce. It can be inferred that the reason is that, even if the anionic species with high intensity of conjugated acid is released by ionic photoacid generator in the storage of composition (X), the exchange reaction of acid participated by other ionic photoacid generators is also easy to release the anionic species with low intensity of conjugated acid, therefore, the concentration of the anionic species with high intensity of conjugated acid in composition (X) is not easy to improve. In addition, even if the composition (X) is irradiated with ultraviolet rays, it is not easy to cause excessively violent curing of the composition (X), and therefore, it is not easy to cause deterioration of transparency due to white turbidity, etc. in the cured product. It is estimated that the reason is that even if the ionic photoacid generator releases anionic species with high strength of the conjugate acid by irradiation with ultraviolet rays, it is easy to release anionic species with low strength of the conjugate acid by the same mechanism as the above-mentioned case, and therefore, an excessively violent reaction caused by anionic species with high strength of the conjugate acid can be suppressed.

[0140] The cationic curing catalyst (G) preferably contains a first agent (g1) containing an ionic photoacid generator having an anion species with a higher conjugate acid strength, and a second agent (g2) containing an ionic photoacid generator having an anion species with a lower conjugate acid strength.

[0141] The first agent (g1) particularly preferably contains an ionic photoacid generator having an anion species with a conjugate acid strength greater than that of HSbF6. In addition, the second agent (g2) particularly preferably contains an ionic photoacid generator having an anion species with a conjugate acid strength lower than that of HSbF6, and further preferably contains an ionic photoacid generator having an anion species with a strength less than that of HPF6.

[0142] The first agent (g1) contains, for example, a compound selected from the group consisting of (Rf) n PF 6-n - Ionic photoacid generator with (Rx) n BX 4-n - Ionic photoacid generator, and having (Rx) n GaX 4-n - At least one ionic photoacid generator selected from ionic photoacid generators such as PF6 -Ionic photoacid generator with BF4 - Ionic photoacid generator with (Rf)SO3 - At least one ionic photoacid generator selected from the group consisting of an ionic photoacid generator having sulfite ions and the like.

[0143] It should be noted that (Rf) n PF 6-n - and (Rf)SO3 - Rf in is a perfluoroalkyl group, (Rf) n PF 6-n - Where n is any number from 1 to 5. (Rf) n PF 6-n - The carbon number of Rf in (Rf)SO3 is, for example, 1 or more and 3 or less. When there are multiple Rf, they may be the same or different. - The carbon number of Rf in is, for example, 1 or more and 8 or less.

[0144] (Rx) n BX 4-n - and (Rx) n GaX 4-n - Rx in each case is a phenyl group in which a part of the hydrogen atoms is substituted by a halogen atom or an electron-withdrawing substituent. The halogen atom is a fluorine atom, a chlorine atom or a bromine atom. The electron-withdrawing substituent is, for example, a trifluoromethyl group, a nitro group or a cyano group. (Rx) n BX 4-n - and (Rx) n GaX 4-n - X in each case is a halogen atom, preferably a fluorine atom. (Rx) n BX 4-n - and (Rx) n GaX 4-n - In each case, n is any number from 1 to 4. When there are multiple Rx, Rx may be the same or different from each other. Rx is, for example, C6F6, (CF3)2C6H3, CF3C6H4, or C6H3F2. (Rx) n BX 4-n - For example, (C6F5)4B - 、((CF3)2C6H3)4B - 、(CF3C6H4)4B - 、(C6F5)2BF2- 、C6F5BF3 - or (C6H3F2)4B - wait.

[0145] The cationic curing catalyst (G) contains PF6 - In the case of an ionic photoacid generator, PF6 - The amount of the ionic photoacid generator is preferably 50% by mass or less relative to the total amount of the cationic curing catalyst (G). - A small amount of hydrofluoric acid is produced, which may corrode inorganic materials such as silicon nitride and silicon oxide used as passivation layer materials. - As described above, when the amount of the ionic photoacid generator is 50 mass % or less, the risk of corrosion of the inorganic material by hydrofluoric acid can be reduced.

[0146] The cationic curing catalyst (G) contains a catalyst having (Rf) n PF 6-n - In the case of an ionic photoacid generator having (Rf) n PF 6-n - The amount of the ionic photoacid generator is preferably 75% by mass or less relative to the total amount of the cationic curing catalyst (G). - There are so many cases, but sometimes (Rf) n PF 6-n - A small amount of hydrofluoric acid is also produced. However, n PF 6-n - As described above, when the amount of the ionic photoacid generator is 75 mass % or less, the risk of corrosion of the inorganic material by hydrofluoric acid can be reduced.

[0147] In addition, the cationic curing catalyst (G) contains PF6 - Ionic photoacid generator and having (Rf) n PF 6-n - In the case of using both of the ionic photoacid generator and the ionic photoacid generator, the total amount of these ionic photoacid generators is preferably 80% by mass or less based on the total amount of the cationic curing catalyst (G).

[0148] On the other hand, with (Rx) n BX 4-n - Ionic photoacid generator and (Rx) n GaX 4-n -An ionic photoacid generator is preferred because it is less likely to generate hydrofluoric acid.

[0149] The cationic species in the ionic photoacid generator contained in the first agent (g1) and the cationic species in the ionic acid generator contained in the second agent (g2) are not particularly limited and can be, for example, at least one selected from various aromatic oniums, more specifically various aromatic diazo oniums, aromatic halogen oniums, and aromatic sulfoniums.

[0150] When the cationic curing catalyst (G) contains the first agent (g1) and the second agent (g2), the composition (X) has good curability, and the cured product of the composition (X) is particularly unlikely to become turbid, and the storage stability of the composition (X) is particularly likely to be high.

[0151] The ratio of the first agent (g1) relative to the total amount of the first agent (g1) and the second agent (g2) is preferably 50% by mass or more. In this case, the composition (X) can have good curability. In addition, the ratio is preferably 90% by mass or less. In this case, it is particularly difficult to produce white turbidity in the cured product, and the storage stability of the composition (X) is particularly easy to become high. If the ratio is 60% by mass or more and 90% by mass or less, it is more preferred, and if it is 70% by mass or more and 85% by mass or less, it is further preferred.

[0152] In addition, in this embodiment, the strength of the conjugate acid of the compound contained in the cationic curing catalyst (G) may be the same. That is, for example, the cationic curing catalyst (G) may contain only one kind of compound.

[0153] The ratio of the cationic curing catalyst (G) relative to the total amount of the resin component is preferably 1% by mass or more and 4% by mass or less. By this ratio being 1% by mass or more, the composition (X) can have particularly good cationic polymerization reactivity. In addition, by this ratio being 4% by mass or less, the composition (X) can have good storage stability, and in addition, by not containing an excessive cationic curing catalyst (G), the manufacturing cost can be reduced.

[0154] The composition (X) may contain a sensitizer (H). The sensitizer (H) contains, for example, either or both of 9,10-dibutoxyanthracene and 9,10-diethoxyanthracene. The ratio of the sensitizer (H) relative to the total amount of the resin component is preferably in the range of more than 0% by mass and less than 1% by mass. In this case, the sensitizer (H) is not likely to hinder the transparency of the cured product, and therefore, the cured product can have good transparency. It is further preferred that the amount of the sensitizer (H) is more than 0% by mass and less than 0.8% by mass relative to the total amount of the resin component.

[0155] Composition (X) may further contain hygroscopic agent (C). If composition (X) contains hygroscopic agent (C), the cured product may have excellent hygroscopicity. Preferably, the average particle size of hygroscopic agent (C) is less than 200nm. In this case, despite containing hygroscopic agent (C), the cured product may also have high transparency. In addition, particularly when composition (X) is ejected by inkjet method, if the average particle size of hygroscopic agent (C) is less than 200nm, there is an advantage that composition (X) is not easy to clog the nozzle. Furthermore, if the average particle size of hygroscopic agent (C) is less than 200nm, hygroscopic agent (C) is not easy to damage the smoothness of the surface of the optical component made by composition (X). Therefore, the surface of the optical component may have good smoothness.

[0156] As described above, by using a hygroscopic agent (C), the cured product can have high hygroscopicity. The moisture absorption rate of the cured product is preferably 0.5% by mass or more, more preferably 1% by mass or more, and most preferably 2% by mass or more. It should be noted that the moisture absorption rate can be obtained by the following method. After applying the composition (X) in an argon atmosphere, ultraviolet rays are irradiated to produce a film with a thickness of 10 μm. The ultraviolet irradiation conditions are: for example, the peak wavelength of the ultraviolet rays is 365nm, the ultraviolet intensity is 3000mW / cm 2 , ultraviolet irradiation time is 10 seconds. The film is vacuum dried, for example, using a vacuum dryer under the conditions of a heating temperature of 120°C and a heating time of 3 hours. The mass of the dried film is measured. The measurement result is referred to as the initial mass (M0). Next, the film is fully humidified. To this end, for example, the film is exposed to the conditions of 85°C and 85%RH for 24 hours. The mass of the film after moisture absorption is measured. The measurement result is referred to as the mass after moisture absorption (M). The moisture absorption rate can be calculated from the initial mass (M0) and the mass after moisture absorption (M) using the formula (M-M0) / M0×100 (mass %).

[0157] The moisture absorbent (C) is preferably an inorganic particle having moisture absorbency, and preferably contains at least one component selected from, for example, zeolite particles, silica gel particles, calcium chloride particles, and titanium oxide nanotube particles. In particular, the moisture absorbent (C) preferably contains zeolite particles.

[0158] The zeolite particles with an average particle size of less than 200 nm can be manufactured, for example, by crushing a general industrial zeolite. When manufacturing the zeolite particles, the zeolite can be crystallized by hydrothermal synthesis or the like after being crushed. In this case, the zeolite particles can have particularly high hygroscopicity. As a method for manufacturing such nano-sized zeolite particles, for example, methods disclosed in Japanese Patent Publication No. 2016-69266 and Japanese Patent Publication No. 2013-049602 can be used.

[0159] The zeolite particles are preferably made of a zeolite containing sodium ions as a raw material, and more preferably made of at least one selected from type A zeolite, type X zeolite, and type Y zeolite among the zeolites containing sodium ions as a raw material. The zeolite particles are particularly preferably made of type 4A zeolite among type A zeolite as a raw material. In these cases, the zeolite particles have a crystal structure suitable for adsorption of water.

[0160] A specific example of a method for producing zeolite particles with an average particle size of less than 200 nm is shown. First, zeolite powder as a raw material is prepared, and the zeolite powder is physically crushed. For example, zeolite powder is mixed with water to prepare a slurry, and the slurry is added to a bead mill, thereby physically crushing the zeolite powder.

[0161] Next, the zeolite powder is crystallized by hydrothermal synthesis. For example, the hydrothermal synthesis can be performed by heating a slurry containing physically crushed zeolite powder in an autoclave. The conditions of the hydrothermal synthesis are, for example, a heating temperature in the range of 150 to 200° C. and a heating time in the range of 15 to 24 hours.

[0162] Next, the zeolite powder is dried. The drying temperature is, for example, in the range of 150 to 200° C., and the drying time is, for example, in the range of 2 to 3 hours. Next, the dried zeolite powder is pulverized using a mortar or the like as needed, and then sieved to adjust the particle size.

[0163] Next, the zeolite powder is subjected to an ion exchange treatment as necessary. In particular, when the zeolite powder is a sodium-containing zeolite such as LTA, it is preferable to perform an ion exchange treatment to exchange the sodium in the zeolite powder with magnesium.

[0164] The ion exchange treatment is carried out, for example, by dispersing zeolite powder in an aqueous solution containing magnesium ions to prepare a mixture, and heating the mixture. More specifically, the ion exchange treatment is carried out, for example, as described below. First, zeolite powder is mixed with magnesium chloride and water, and a treatment is carried out while the resulting mixture is heated and stirred. During the treatment, the following operation is preferably repeated multiple times at appropriate intervals: the supernatant of the mixture is discarded after temporarily stopping the stirring, and then water is added to the mixture, and then the stirring operation is started again. The heating temperature in the treatment is preferably in the range of 40 to 80°C, and the treatment time is preferably in the range of 6 to 8 hours.

[0165] When the ion exchange treatment is performed, the zeolite powder is then dried. The drying temperature is, for example, in the range of 150 to 200° C., and the drying time is, for example, in the range of 2 to 3 hours. Next, the dried zeolite powder is crushed using a mortar or the like as needed, and then sieved to adjust the particle size. Thus, zeolite particles with an average particle size of 200 nm or less can be obtained.

[0166] The crystallization of zeolite powder can also be carried out in the presence of silicates and alkali metal oxides. A specific example of a method for producing zeolite particles having an average particle size of 200 nm or less in this case is shown. First, zeolite powder is prepared. The zeolite powder preferably has a composition of aM12O·bSiO2·Al2O3·cMe. M1 is an alkali metal, a proton or an ammonium ion (NH4 + ), Me is an alkaline earth metal, a is a number in the range of 0.01 to 1, b is a number in the range of 20 to 80, and c is a number in the range of 0 to 1. The zeolite powder preferably contains a zeolite containing sodium ions, and more preferably contains at least one material selected from type A zeolite, type X zeolite and type Y zeolite among the zeolites containing sodium ions. The zeolite powder particularly preferably contains type 4A zeolite among type A zeolite. The zeolite powder is physically crushed. For example, the zeolite powder can be physically crushed by adding the zeolite powder to a bead mill.

[0167] The physically crushed zeolite powder is dispersed in a solution containing M22O, SiO2 and H2O to prepare a slurry. M2 is an alkali metal, preferably K or Na. The molar ratio of M22O / H2O is, for example, in the range of 0.003 to 0.01, and the molar ratio of SiO2 / H2O is, for example, in the range of 0.006 to 0.025. The amount of zeolite powder is, for example, 0.5 to 10 g in 100 ml of the solution.

[0168] The slurry is heated in an autoclave to crystallize the zeolite powder. The conditions are, for example, a heating temperature in the range of 100 to 230° C. and a heating time in the range of 1 to 24 hours. Next, the zeolite powder is washed and then dried. Thus, zeolite particles with an average particle size of less than 200 nm can be obtained.

[0169] The pH of the zeolite particles is preferably 7 or more and 10 or less. If the pH of the zeolite particles is 7 or more, the crystals of the zeolite particles become less likely to be destroyed, and therefore, the optical component made from the composition (X) containing the zeolite particles can have particularly high hygroscopicity. In addition, if the pH of the zeolite particles is 10 or less, when the composition (X) is cured, the zeolite particles are less likely to hinder the curing.

[0170] The pH of the zeolite particles is a value obtained by heating a dispersion obtained by adding 0.05 g of zeolite particles to 99.95 g of ion-exchanged water at 90° C. for 24 hours, and then measuring the pH of the supernatant of the dispersion using a pH meter. As the pH meter, for example, a compact pH meter manufactured by Horiba, Ltd. can be used. <laquatwin>B-711.

[0171] In order to adjust the pH of the zeolite particles to 7 or more and 10 or less, the zeolite particles preferably contain FAU Y-type zeolite having protons as counter cations.

[0172] In the process of producing zeolite particles, when hydrothermal synthesis of zeolite is performed, a treatment for adjusting pH may be performed. The treatment for adjusting pH may be performed, for example, before heating the slurry containing the zeolite powder prepared for hydrothermal synthesis, during the heating of the slurry, or after the heating of the slurry. The pH is adjusted, for example, by adding an acid to the slurry. The acid may contain, for example, at least one component selected from an inorganic acid such as hydrochloric acid, sulfuric acid, and nitric acid, and an organic acid such as formic acid, acetic acid, and oxalic acid.

[0173] The average particle size of the hygroscopic agent (C) is preferably 10 nm or more and 200 nm or less. If the average particle size is 200 nm or less, the cured product can have particularly high transparency. In addition, if the average particle size is 10 nm or more, the good hygroscopicity of the hygroscopic agent (C) can be maintained. It should be noted that the average particle size is the median particle size calculated from the measurement results based on the dynamic light scattering method, that is, the cumulative 50% diameter (D50). It should be noted that as a measuring device, the Nanotrac Wave series of MicrotracBELCorp. can be used.

[0174] The average particle size of the hygroscopic agent (C) is more preferably below 150 nm, and is further preferably below 100 nm, and is particularly preferably below 70 nm. In addition, the average particle size of the hygroscopic agent (C) is preferably above 20 nm, and is more preferably above 50 nm. In this case, the cured product can have particularly good transparency and hygroscopicity.

[0175] It is also preferred that the cumulative 90% diameter (D90) of the moisture absorbent (C) is 100 nm or less. In this case, the cured product can have particularly high transparency.

[0176] The ratio of the hygroscopic agent (C) relative to the total amount of the composition (X) is preferably 1% by mass or more and 20% by mass or less. If the ratio of the hygroscopic agent (C) is 1% by mass or more, the cured product can have a particularly high hygroscopicity. In addition, if the ratio of the hygroscopic agent (C) is 20% by mass or less, the viscosity of the composition (X) can be particularly reduced, and the composition (X) can also have a sufficiently low viscosity to the extent that it can be ejected using an inkjet method. If the ratio of the hygroscopic agent (C) is 3% by mass or more, it is further preferred, and if it is 5% by mass or more, it is particularly preferred. In addition, if the ratio of the hygroscopic agent (C) is 15% by mass or less, it is more preferred, and if it is 13% by mass or less, it is particularly preferred.

[0177] The composition (X) may further contain inorganic fillers other than the hygroscopic agent (C). In particular, the composition (X) preferably contains nano-sized high refractive index particles. Examples of high refractive index particles include zirconium oxide particles. If the composition (X) contains high refractive index particles, it is possible to maintain the good transparency of the cured product while making the cured product have a high refractive index. Therefore, when the cured product is applied to optical components such as the sealing material 5 in the light-emitting device 1, the extraction efficiency of light emitted to the outside through the transmitted optical components can be improved. The average particle size of the high refractive index particles is preferably in the range of 5 to 30 nm, and is further preferred if it is in the range of 10 to 20 nm.

[0178] The proportion of high refractive index particles in the composition (X) can be suitably designed so that the cured product has a desired refractive index. In particular, it is preferred that the high refractive index particles are included in the composition (X) in such a manner that the refractive index of the cured product is within a range of 1.45 or more and less than 1.55. In this case, the light extraction efficiency of the light emitting device 1 is particularly improved.

[0179] In the case where the composition (X) contains a hygroscopic agent (C), the composition (X) may further contain a dispersant (D). The dispersant (D) is a surfactant that can be adsorbed on the hygroscopic agent (C). The dispersant (D) has, for example, an adsorption group (also referred to as an anchor) that can be adsorbed on particles of the hygroscopic agent (C) and a tail of a molecular skeleton in a chain or comb shape that is attached to the particles of the hygroscopic agent (C) by adsorption of the adsorption group. The dispersant (D) contains, for example, at least one component selected from an acrylic dispersant having an acrylic molecular chain as the tail, a carbamate dispersant having a carbamate molecular chain as the tail, and a polyester dispersant having a polyester molecular chain as the tail.

[0180] If the composition (X) contains a dispersant (D), the hygroscopic agent (C) can be well dispersed in the composition (X) and the cured product. Therefore, although the cured product and the optical component contain a hygroscopic agent (C), the transparency of the cured product and the optical component is not easily reduced by the hygroscopic agent (C). In addition, the dispersant (D) can effectively suppress the aggregation of the hygroscopic agent (C) during the storage of the composition (X). Therefore, the storage stability of the composition (X) is not easily reduced by the hygroscopic agent (C).

[0181] Furthermore, the adhesion between the cured product and silicon nitride and silicon oxide is not easily reduced by the dispersant (D). It can be considered that the reason is that, as mentioned above, the dispersant (D) is easily adsorbed on the hygroscopic agent (C), so the dispersant (D) is not easy to affect the interface between the cured product and silicon nitride and silicon oxide. Therefore, the optical component can have a high adhesion with a glass substrate. In addition, silicon nitride and silicon oxide are sometimes used as the material of the passivation layer 6 in the light-emitting device 1. Therefore, when the passivation layer 6 is made of silicon nitride or silicon oxide, the optical components such as the sealing material 5 can have a high adhesion with the passivation layer 6.

[0182] The boiling point of the dispersant (D) is preferably 200° C. or higher. In this case, the dispersant (D) is less likely to volatilize from the composition (X), and thus the storage stability of the composition (X) is further improved.

[0183] The dispersant (D) preferably has either or both of a basic polar functional group and an acidic polar functional group as an adsorption group. In this case, the hygroscopic agent (C) can be particularly well dispersed in the composition (X) and the cured product. It is believed that the reason is that the dispersant (D) has either or both of a basic polar functional group and an acidic polar functional group, and thus is easily adsorbed on the hygroscopic agent (C), so that the effect of dispersing the hygroscopic agent (C) is significantly manifested.

[0184] The dispersant (D) may contain a polymer. The weight average molecular weight of the polymer is, for example, 1000 or more. The polymer contains, for example, a hydroxyl-containing carboxylic acid ester, a salt of a long-chain polyaminoamide and a high molecular weight acid ester, a salt of a high molecular weight polycarboxylic acid, a salt of a long-chain polyaminoamide and a polar acid ester, a high molecular weight unsaturated acid ester, a modified polyurethane, a modified polyacrylate, a polyether ester type anionic active agent, a salt of a naphthalenesulfonic acid formaldehyde condensate, a polyoxyethylene alkyl phosphate, a polyoxyethylene nonylphenyl ether, a polyester polyamine, and at least one component of stearylamine acetate. If the dispersant (D) contains a polymer, the steric hindrance effect generated when the polymer is adsorbed on the particles of the hygroscopic agent (C) is increased, thereby being able to improve the dispersibility of the hygroscopic agent (C).

[0185] The dispersant (D) may contain, for example, either or both of a dispersant (F1) having a basic polar functional group and a dispersant (F2) having an acidic polar functional group.

[0186] The basic polar functional group in the dispersant (F1) having a basic polar functional group includes, for example, at least one group selected from an amino group, an imino group, an amide group, an imide group, and a nitrogen-containing heterocyclic group. If the dispersant (F1) has a basic polar functional group, the dispersant (F1) is easily adsorbed on the hygroscopic agent (C), and thus the dispersibility of the hygroscopic agent (C) can be improved. From the perspective of being able to particularly improve the adsorption capacity of the dispersant (F1) to the hygroscopic agent (C), being able to particularly improve the dispersibility of the hygroscopic agent (C), and being able to particularly reduce the viscosity of the composition (X), the basic polar functional group preferably includes an amino group.

[0187] The dispersant (F1) having a basic polar functional group includes, for example, Solsperse 24000 (amine value: 41.6 mgKOH / g), Solsperse 32000 (amine value: 31.2 mgKOH / g), Solsperse 39000 (amine value: 25.7 mgKOH / g), Solsperse J100, Solsperse J200 and other Solsperse series made by Japan Lubrizol Corporation; trade names: DISPERBYK-108, DISPERBYK-2013, DISPERBYK-180, DISPERBYK-106, DISPERBYK-162 (amine value: 13 mgKOH / g), trade name: DISPERBYK-163 (amine value: 10 mgKOH / g), trade name: DISPERBYK-168 (amine value: 11 mgKOH / g), trade name: DISPERBYK-2050 (amine value: 30. 7 mgKOH / g), DISPERBYK series manufactured by BYK-CHEMIE JAPAN Co., Ltd., such as trade name: DISPERBYK-2150 (amine value: 56.7 mgKOH / g); BYKJET series manufactured by BYK-CHEMIE JAPAN Co., Ltd., such as trade name: BYKJET-9151 (amine value: 17.2 mgKOH / g), trade name: BYKJET-9152 (amine value: 27.3 mgKOH / g); and AJISPER series manufactured by Ajinomoto Fine-Techno Co., Inc., such as trade name: AJISPERP B821 (amine value: 11.2 mgKOH / g), trade name: AJISPER PB822 (amine value: 18.2 mgKOH / g), and trade name: AJISPERP B881 (amine value: 17.4 mgKOH / g).

[0188] The amine value of the dispersant (F1) is preferably 10 mgKOH / g or more, more preferably 10 mgKOH / g or more and 30 mgKOH / g or less, and further preferably 15 mgKOH / g or more and 30 mgKOH / g or less. In addition, the dispersant (F1) preferably does not have a phosphate group. In the case where the dispersant (F1) has a phosphate group, it is preferred that the acid value from the phosphate group is less than the value of the amine value. In this case, the dispersant (F1) can make the hygroscopic agent (C) particularly well dispersed, can particularly improve the storage stability of the composition (X), can particularly improve the transparency of the cured product, and further can particularly improve the adhesion between the cured product and silicon nitride and silicon oxide. Among the components that the dispersant (F1) can contain, examples of dispersants having an amino group and not having a phosphate group include DISPERBYK-108 manufactured by BYK-CHEMIE. Examples of the dispersant having an amino group and a phosphoric acid group and having an acid value derived from the phosphoric acid group equal to or less than the amine value include DISPERBYK-2013 manufactured by BYK-CHEMIE and DISPERBYK-180 manufactured by BYK-CHEMIE.

[0189] The acidic polar functional group in the dispersant (F2) having an acidic polar functional group is, for example, a carboxyl group. The dispersant (F2) contains, for example, DISPERBYK-P105 manufactured by BYK-CHEMIE.

[0190] The amount of dispersant (D) relative to 100 parts by mass of hygroscopic agent (C) is preferably 5 parts by mass or more and 60 parts by mass or less. If the amount of dispersant (D) is 5 parts by mass or more, the advantages of dispersant (D) can be particularly brought into play. If the amount of dispersant (D) is 60 parts by mass or less, the adhesion between the cured product and silicon nitride and silicon oxide can be further improved. If the amount of dispersant (D) is 15 parts by mass or more, it is more preferred. If the amount of dispersant (D) is 50 parts by mass or less, it is more preferred, if it is 40 parts by mass or less, it is further preferred, and if it is 30 parts by mass or less, it is particularly preferred.

[0191] Composition (X) preferably does not contain solvent, or the content of solvent is 1% by mass or less. In this case, when making a cured product from composition (X), it is not necessary to dry composition (X) and volatilize the solvent. In addition, the storage stability of composition (X) further becomes higher. If the content of solvent is 0.5% by mass or less, it is more preferred, if it is 0.3% by mass or less, it is further preferred, if it is 0.1% by mass or less, it is particularly preferred. Particularly preferably, composition (X) does not contain solvent, or only contains the solvent inevitably mixed in.

[0192] The composition (X) can be prepared by mixing the above components. It is preferred that the composition (X) is in a liquid state at 25°C.

[0193] 3. Method for manufacturing sealing material and method for manufacturing light-emitting device

[0194] A method for producing the sealing material 5 and a method for producing the light-emitting device 1 using the composition (X) will be described.

[0195] In the present embodiment, it is preferred that the composition (X) is ejected by an inkjet method to form a coating film on an object, and then the coating film is irradiated with ultraviolet rays and then heated to produce the sealing material 5. In the present embodiment, the composition (X) is ejected from an inkjet head to form a coating film by coating on an object.

[0196] When the composition (X) is applied to an object by ejecting it by an inkjet method, if the composition (X) has a sufficiently low viscosity at room temperature, for example, a viscosity of 30 mPa·s or less, particularly 15 mPa·s or less at 25° C., the composition (X) can be ejected by an inkjet method and applied to the object without heating it.

[0197] When the composition (X) has a property of being reduced in viscosity by being heated, the composition (X) can be heated and then sprayed by an inkjet method to be applied to an object. When the viscosity of the composition (X) at 40° C. is 30 mPa·s or less, particularly 15 mPa·s or less, the viscosity of the composition (X) can be reduced by only slightly heating the composition (X), and the composition (X) with reduced viscosity can be sprayed by an inkjet method. The heating temperature of the composition (X) is, for example, 20° C. or more and 50° C. or less.

[0198] When the coating film formed by the composition (X) is irradiated with light and cured, the light irradiated to the coating film is, for example, ultraviolet light. Ultraviolet light refers to light with a wavelength of more than 200nm and less than 410nm. The wavelength of the light irradiated to the coating film is preferably within the range of more than 350nm and less than 410nm, and if it is more than 385nm and less than 405nm, it is further preferred. As one of the representative examples of the light irradiated to the coating film, light with a wavelength of 395nm can be cited. It should be noted that the wavelength of the light irradiated to the coating film is not limited to the above description as long as it is a wavelength that can cure the coating film.

[0199] The irradiation intensity of the light irradiated to the coating film is preferably 20 mW / m 2 Above and 20W / cm 2 It should be noted that the irradiation intensity of light is not limited to the above description as long as it is an intensity that can cure the coating film.

[0200] When the coating film is irradiated with light, the shape of the portion irradiated with light may be a region type having a certain degree of area or a line type. In the case of the line type, the coating film can be irradiated with light as a whole by moving the coating film relative to the light source or by moving the light source relative to the coating film. In this case, it is easy to adjust the time for irradiating the coating film with light, and by adjusting the time, it is easy to adjust the accumulated light amount.

[0201] The heating temperature when further heating the cured coating film is preferably 90° C. or higher. In this case, the coating film is further cured, and the linear expansion coefficient of the sealing material 5 is easily reduced, thereby making it easy to achieve a linear expansion coefficient of the sealing material 5 of 100 ppm / ° C. or higher and 130 ppm / ° C. or lower. The heating temperature is preferably 150° C. or lower. In this case, the organic EL element or the like as the light emitting element 4 is not easily degraded by heat.

[0202] More specifically, for example, a supporting substrate 2 is first prepared. On one surface of the supporting substrate 2, for example, a partition wall is formed by photolithography using a photosensitive resin material. Next, a plurality of organic EL elements or the like as light-emitting elements 4 are provided on one surface of the supporting substrate 2. The organic EL elements or the like as light-emitting elements 4 can be produced by a suitable method such as a vapor deposition method or a coating method. It is particularly preferred to produce the organic EL elements or the like as light-emitting elements 4 by a coating method such as an inkjet method in the same manner as the composition (X). Thus, an element array 9 is produced on the supporting substrate 2.

[0203] Next, the first passivation layer 61 is provided on the element array 9. The first passivation layer 61 can be formed by, for example, a vapor deposition method such as a plasma CVD method.

[0204] Next, the composition (X) is ejected on the first passivation layer 61 by, for example, an inkjet method to form a coating film. If the inkjet method is applied to either the formation of an organic EL element or the like as the light-emitting element 4 or the coating of the composition (X), the manufacturing efficiency of the light-emitting device 1 can be particularly improved. Next, the coating film is cured by irradiating ultraviolet rays to form a sealing material 5. The thickness of the sealing material 5 is, for example, not less than 2 μm and not more than 50 μm.

[0205] The thickness of the sealing material 5 is also preferably 2 μm or more and 30 μm or less, and more preferably 2 μm or more and 15 μm or less. As described above, in the present embodiment, it is easy to form small droplets of the composition (X) at a high density by inkjet method, so it is easy to realize a thin sealing material 5 of 2 μm or more and 15 μm or less. If the sealing material 5 is thinned as described above, it is not easy for the sealing material 5 to generate tensile stress and compressive stress in the light-emitting device 1. Therefore, it is easy to realize a flexible light-emitting device 1.

[0206] Next, the second passivation layer 62 is provided on the sealing material 5. The second passivation layer 62 can be formed by, for example, a vapor deposition method such as a plasma CVD method.

[0207] Next, an ultraviolet curable resin material is provided on one surface of the support substrate 2 so as to cover the second passivation layer 62, and then the transparent substrate 3 is stacked on the resin material. The transparent substrate 3 is, for example, a glass substrate or a transparent resin substrate.

[0208] Next, ultraviolet rays are irradiated from the outside to the transparent substrate 3. The ultraviolet rays pass through the transparent substrate 3 and reach the ultraviolet curable resin material. As a result, the ultraviolet curable resin material is cured, and the second sealing material 52 is produced.

[0209] As described above, the sealing material 5 comprising the cured product of the composition (X) can have good heat resistance. Therefore, when the passivation layer 6 (second passivation layer 62) is made by a vapor deposition method such as a plasma CVD method and overlapped with the sealing material 5, even if the temperature of the sealing material 5 rises, the sealing material 5 is not easy to deteriorate. In addition, even if the temperature of the light-emitting device 1 rises when the light-emitting device 1 is used, the sealing material 5 is not easy to deteriorate. It should be noted that, as described above, the light-emitting element 4 is, for example, an organic EL element, but the light-emitting element 4 may also be a micro light-emitting diode or the like.

[0210] It should be noted that the optical component is not limited to the sealing material 5 for the light-emitting element 4. The composition (X) can be used to make various optical components. For example, the optical component can be a color resist. In this case, for example, a fluorescent substance is contained in the composition (X), and the color resist in the color filter is made from the composition (X). In this case, it is easy to make the color resist in the color filter with high density and good precision. The color filter can be set in a display device such as an organic EL display or a micro LED display.

[0211] Example

[0212] Specific examples of the present application are presented below, but the present application is not limited to the following examples.

[0213] 1. Preparation of the composition

[0214] The compositions of Examples and Comparative Examples were prepared by mixing the components shown in the following table.

[0215] The details of the components shown in the table are as follows. The viscosity of the following components was measured using a rheometer (Anton Paar Japan, Model DHR-2) at a temperature of 25°C and a shear rate of 1000 s. -1 The value measured under the conditions of .

[0216] (1) Cationic polymerizable compounds

[0217] ■ Phenylmethylethylene oxide: boiling point 235°C, viscosity 6 mPa·s at 25°C.

[0218] ■4-Fluorophenylethylene oxide: boiling point 220°C, viscosity 8 mPa·s at 25°C.

[0219] ■Styrene oxide: boiling point 200°C, viscosity 4 mPa·s at 25°C.

[0220] ■BATG: a polyfunctional aromatic epoxy compound, manufactured by Showa Denko, model BATG, boiling point 300°C or higher, viscosity at 25°C 10,000 mPa·s.

[0221] ■2-Glycidyl-phenyloxirane has a boiling point of 300°C or higher and a viscosity of 17 mPa·S at 25°C.

[0222] ■OXT-221: manufactured by Toa Gosei, model number OXT-221, a compound represented by formula (3), boiling point 275°C, surface tension 33 mN / cm, viscosity 11 mPa·s.

[0223] ■OXT-212: manufactured by Toa Gosei, model number OXT-212, a compound represented by formula (12), boiling point 277°C, surface tension 35 mN / cm, viscosity 4 mPa·s.

[0224] ■AL-EOX: manufactured by Yokkaichi Kogyo Co., Ltd., model number AL-EOX, a compound represented by formula (16), boiling point 200°C, surface tension 27 mN / cm, viscosity 2 mPa·s.

[0225] ■CELLOXIDE 8010: manufactured by Daicel, product name CELLOXIDE 8010, a compound represented by formula (1a), boiling point 265°C, surface tension 43 mN / cm, viscosity at 25°C 60 mPa·s.

[0226] ■CELLOXIDE 8010 (heat-treated product): The above-mentioned CELLOXIDE 8010 was heat-treated at 100° C. for 30 minutes in an air atmosphere, with a boiling point of 265° C., a surface tension of 43 mN / cm, and a viscosity of 60 mPa·s at 25° C.

[0227] ■1,2,7,8-Octane diepoxide: boiling point 230°C, surface tension 37 mN / cm, viscosity at 25°C 3 mPa·s.

[0228] (2) Cationic curing catalyst

[0229] ■CPI-310B: Made by San-Apro, triarylsulfonium salt type photoacid generator, anion species B (C6F5)4 - , model CPI-310B.

[0230] ·CPI-210S: Triarylsulfonium salt type photoacid generator, anion species (Rf) manufactured by San-Apro n PF 6-n - , model CPI-310B.

[0231] ·IK-1: Made by San-Apro, diaryliodonium salt type photoacid generator, anion species (Rf) n PF 6-n , model IK-1.

[0232] ·CPI-110P: Triarylsulfonium salt-type photoacid generator, anion species PF6, manufactured by San-Apro - , model CPI-110P.

[0233] · IRGACURE250: Made by BASF, diaryliodonium salt type photoacid generator, anion species PF6 - , model IRGACURE250.

[0234] (3) Sensitizer

[0235] UVS1331: 9,10-dibutoxyanthracene, manufactured by Kawasaki Chemical Co., Ltd., model number UVS1331.

[0236] DETX-s: 2,4-diethylthioxanthen-9-one, manufactured by Nippon Kayaku Co., Ltd., model number DETX-s.

[0237] (4) Additives

[0238] BYK333: Leveling agent, manufactured by BYK-CHEMIE, active ingredient: polyether-modified polydimethylsiloxane.

[0239] 2. Evaluation test

[0240] The following evaluation tests were carried out on the Examples and Comparative Examples, and the results are shown in the table.

[0241] 2.1. Curing

[0242] The composition was applied to a slide glass, and then an LED-UV irradiator manufactured by CCS Corporation was used at a peak wavelength of 395 nm and an output power of 1 W / cm 2 Under the condition of 1.5J / cm 2 The film was irradiated with light in a manner of a certain amount of light, thereby photocuring it. The atmosphere was set to a dry atmosphere containing oxygen. Thus, a film with a thickness of 10 μm was produced. The tester touched the surface of the film with a finger to determine whether it was sticky. As a result, the tester evaluated the case where the tester did not feel stickiness as "A", the case where the film was not attached to the finger but felt sticky as "B", and the case where the film felt sticky and part of it was attached to the finger as "C".

[0243] 2.2. Transmittance

[0244] The composition was applied on a smooth surface, and then an LED-UV irradiator manufactured by CCS Corporation was used in a dry atmosphere at a peak wavelength of 395 nm and an output power of 1 W / cm 2 , cumulative light volume 1.5J / cm 2 The film was irradiated with light under the conditions of , thereby photocuring it. Thus, a film with a thickness of 15 μm was produced. The transmittance of light of a wavelength of 430 nm of the film was measured. During the measurement, a spectrophotometer (U-4100 manufactured by Hitachi, Ltd.) was used. It should be noted that in the case of Comparative Example 3, the composition could not be fully photocured, so it could not be evaluated.

[0245] 2.3. Viscosity

[0246] A rheometer (Anton Paar Japan, Model DHR-2) was used at a temperature of 25°C and a shear rate of 1000 s. -1 The viscosity of the composition was measured under the conditions of .

[0247] Surface tension

[0248] The surface tension of the composition was measured by the Wilhelmy method. The measurement was performed using a surface tensiometer (manufactured by Kyowa Interface Science Co., Ltd., model: CBVP-Z) and a platinum plate at a measurement temperature of 25°C.

[0249] 2.5. Storage stability

[0250] The composition was left at 60°C for 2 weeks. The viscosity of the composition before and after the test was measured using a rheometer, and the case where the viscosity change rate was less than 10% was evaluated as "A", the case where the viscosity change rate was 10% or more and gelation of the composition was not observed after the test was evaluated as "B", and the case where gelation of the composition was observed after the test was evaluated as "C".

[0251] 2.6. Inkjetability

[0252] 2.6.1. Satellite drops

[0253] The composition was placed in an ink cartridge of an inkjet printer (RICOH, "MH2420"), and after confirming that the resin composition in the ink cartridge could be ejected from the nozzle of the inkjet printer, the resin composition was ejected from the nozzle to continuously print a test pattern. The appearance of droplets ejected from the nozzle was photographed using a high-speed camera to confirm whether the droplets separated and satellite droplets were generated. As a result, the case where the droplets were not separated was evaluated as "A"; the case where the satellite droplets separated from the original droplets and then integrated with the original droplets to form one droplet again was evaluated as "B"; and the case where the satellite droplets separated from the original droplets but were not integrated was evaluated as "C".

[0254] 2.6.2. Inkjet speed (initial)

[0255] In the test of "2.6.1. Presence or absence of satellite droplets", the droplet ejection velocity was changed to confirm the maximum ejection velocity when the droplets were not separated or when the satellite droplets were separated from the original droplets and then integrated with the original droplets to form one droplet again.

[0256] 2.6.3. Inkjet speed (after storage)

[0257] The composition was stored at a temperature of 60° C. for 2 weeks. Next, the same test as in the above “2.6.2. Inkjet speed (initial)” was performed.

[0258] 2.6.4.Maintenance rate

[0259] The percentage of the result of the above "2.6.3. Ink ejection speed (after storage)" to the result of "2.6.2. Ink ejection speed (initial)" was calculated as the maintenance rate.

[0260] 2.7. Barrier film suitability

[0261] A 500nm thick SiN film was made on a glass slide, and a 10μm thick film was made on the SiN film under the same conditions as in "2.1. Curability". The film was stored in a constant temperature and humidity chamber at 85°C and 85%RH for 168 hours, and then the surface of the film was observed using SEM. As a result, the case where no change was found on the film was evaluated as "A", the case where bulges or surface roughness occurred on the film, but no cracks were found was evaluated as "B", and the case where cracks occurred on the film was evaluated as "C".

[0262] Glass transition temperature

[0263] The composition was applied to form a coating film, and an LED-UV irradiator manufactured by CCS Co., Ltd. was used at a peak wavelength of 395 nm and an output power of 1 W / cm 2 , cumulative light volume 10J / cm 2 The coating film was irradiated with light under the conditions of , thereby preparing a film with a thickness of 200 μm. The glass transition temperature of the sample cut out from the film was measured using a viscoelasticity measuring device (manufactured by Hitachi High-Tech Science Corporation, model DMA7100). It should be noted that in the case of Comparative Example 3, the coating film could not be fully cured, so it could not be evaluated.

[0264] 2.9. Outgassing evaluation

[0265] The outgassing of the cured product of the composition when heated was measured by the following method. 100 mg of the composition was placed in a headspace vial and an LED-UV irradiator manufactured by CCS Corporation was used at a peak wavelength of 395 nm and a power of about 100 mW / cm 2 The composition is irradiated with light under conditions of , and the composition is cured. The vial is then sealed and heated at 80°C for 30 minutes. The gas phase in the vial is then introduced into a gas chromatograph for analysis. The mass ratio of the generated gas relative to the composition is determined from the result. In order to prevent outgassing, the result is preferably 200 ppm or less, more preferably 100 ppm or less, further preferably 50 ppm or less, and particularly preferably 25 ppm or less.

[0266] [Table 1]

[0267]

[0268] [Table 2]

[0269]

[0270] [Table 3]

[0271] < / laquatwin>

Claims

1. An ultraviolet curable resin composition for use in producing an optical component that transmits light emitted from a light source, The ultraviolet curable resin composition contains a cationically polymerizable compound (F) and a cationic curing catalyst (G). The cationically polymerizable compound (F) contains an epoxy compound (f1) and a compound (f22) having an oxyalkylene group and an oxetane group. The epoxy compound (f1) contains a compound (f11) represented by the following formula (30): In formula (30), X is at least one selected from halogen, H, a hydrocarbon group, and an alkylene glycol group. When a plurality of Xs exist in one molecule, Xs are the same or different from each other. R is a single bond or a divalent organic group, Y is H or a monovalent organic group, n is any number from 1 to 3, The ratio of the epoxy compound (f1) is 10% by mass or more and 90% by mass or less relative to the total amount of the cationically polymerizable compound (F), The cationic curing catalyst (G) contains a plurality of ionic photoacid generators having conjugate acids of different anionic species in strength. The cationic curing catalyst (G) comprises a first agent (g1) and a second agent (g2), wherein the first agent (g1) comprises a catalyst selected from the group consisting of (Rf) n PF 6-n - Ionic photoacid generator and (Rx) n BX 4-n - At least one ionic photoacid generator of the ionic photoacid generator, the second agent (g2) comprises a PF6 - Ionic photoacid generator with BF4 - Ionic photoacid generator with (Rf)SO3 - at least one of an ionic photoacid generator having sulfite ions and an ionic photoacid generator having sulfite ions, The Rf are all perfluoroalkyl groups, and the (Rf) n PF 6-n - wherein n is any number from 1 to 5, wherein Rx is a phenyl group in which a portion of hydrogen atoms is substituted by an electron-withdrawing substituent, wherein X is a halogen atom, and wherein (Rx) n BX 4-n - The n in it is any number between 1 and 4.

2. The ultraviolet curable resin composition according to claim 1, wherein The ratio of the compound (f22) to the cationically polymerizable compound (F) is 10% by mass or more.

3. The ultraviolet curable resin composition according to claim 1 or 2, wherein The ratio of the compound (f11) to the total amount of the cationically polymerizable compound (F) is 10% by mass or more and 90% by mass or less.

4. The ultraviolet curable resin composition according to claim 1 or 2, wherein The total amount of the compound (f11) and the compound (f22) is 55% by mass or more based on the cationically polymerizable compound (F).

5. The ultraviolet curable resin composition according to claim 1 or 2, wherein The Rx is a phenyl group in which a part of hydrogen atoms is substituted by halogen atoms.

6. The ultraviolet curable resin composition according to claim 1 or 2, wherein The ratio of the first agent (g1) to the total amount of the first agent (g1) and the second agent (g2) is 50% by mass or more. 7 . The ultraviolet curable resin composition according to claim 1 , which contains no solvent or contains a solvent in an amount of 1% by mass or less. 8 . The ultraviolet curable resin composition according to claim 1 , which has a viscosity at 25° C. of 8 mPa·s or more and 40 mPa·s or less. 9 . The ultraviolet curable resin composition according to claim 1 , which has a viscosity at 40° C. of 8 mPa·s or more and 40 mPa·s or less. 10 . The ultraviolet curable resin composition according to claim 1 or 2 , which can be ejected by an inkjet method.

11. A method for manufacturing a light emitting device, comprising: The optical component is produced by discharging the ultraviolet curable resin composition according to any one of claims 1 to 10 to a position where light emitted from the light source passes by an inkjet method to form a coating film, and irradiating the coating film with ultraviolet light. 12 . A light emitting device comprising a light source and an optical component that transmits light emitted from the light source, wherein the optical component comprises a cured product of the ultraviolet curable resin composition according to claim 1 .

Citation Information

Patent Citations

  • Recovery and refining method of pulp material from urban wastes

    JP1982003429B2

  • Method of manufacturing fine zeolite

    JP2013049602A

  • Production process for nano-zeolite

    JP2016069266A

  • Ultraviolet ray-curable resin composition, method for manufacturing organic el light-emitting device and organic el light-emitting device

    JP2018111792A

  • Optical laminate

    JP2018141962A